Tuning of electronic, optical and lipophilic behaviours of adamantane through various substitutions - Aravindhan R; Jianping Hu; M Ummal Momeen (Materials Research Express)
Successive tuning of electronic, optical and lipophilic characteristics of adamantane molecules are obtained by various halogen substitutions at bridgehead and bridge positions of adamantane. In accordance with this, surface passivated halo adamantanes and dodecahalo adamantanes exhibit impressive tuning of transport properties. In all molecular complexes, electrophilicity and molecular polarizability show progressive growth from fluorine to iodine whereas vertical excitation energies of molecules also follow the same trend. Prominent sigma holes are observed on the outer lobe of bromine and iodine in most of the cases. High hydrophobicity and lipophilicity of the adamantane has a prominent application in medicinal chemistry as a lipophilic bullet for a drug. Through halogen substitution this is more significant in both electropositive and electronegative binding sites exhibited by the anisotropic charge distribution of the halogen.